Identifying and prioritizing barriers to private sector participation in urban management projects - Mohamadreza Abdolalipoor; Roohollah Taherkhani; Alireza Lork (مهندسی و مدیریت ساخت)
Private sector participation, especially in the urban economy and municipal projects, plays a vital role in the development of communities. Undoubtedly, the first step in developing private sector participation in urban management projects is to identify the reasons for reluctance and remove existing barriers to the sector's participation in urban projects. In this regard, the purpose of this study is to identify and evaluate the barriers affecting the non-participation of private companies in investment management projects in Alborz province. The present research is applied research in terms of purpose and descriptive-survey research in terms of method and nature. The method of data collection is based on library studies and field studies, including a researcher-made questionnaire and interviews. The findings of this study indicate that the effective barriers to non-participation of private companies in urban management projects in Alborz province are barriers related to economic, political, legal, social, technical and environmental factors, respectively. Economic factor by preventing fluctuations in inflation and interest rates and foreign exchange market, as the most effective and environmental factor by preventing natural risks including risks related to the climate and climate of the project site, internal and external environmental conditions of the project and force majeure, were identified as the least effective factors.